A type of robust superlattice type-I Weyl semimetal with four Weyl nodes. Issue 39 (1st October 2019) - Meng, Lijun; Wu, Jiafang; Zhong, Jianxin; Römer, Rudolf A.
Abstract : We investigate the topological properties of the Janus superlattices WTeS and WTeSe by first-principles methods and Wannier-based tight-binding Hamiltonians. Abstract : We investigate the topological properties of the Janus superlattices WTeS and WTeSe by first-principles methods and Wannier-based tight-binding Hamiltonians. The thermal stability of the Janus structures is checked by first-principles molecular dynamics. The topological properties are identified through node chirality, surface states and surface Fermi arcs. Our calculations reveal that both WTeS and WTeSe are Type-I Weyl semimetals with only four Weyl nodes in the Brillouin zone, which is a minimal number in a time reversal symmetry system. This small number of Weyl nodes makes them an excellent platform to study their topological properties experimentally. The Weyl nodes are located in four different quadrants of the Brillouin zone and consequently the separation of Weyl points in reciprocal space, and the length of Fermi arc, is of the order of the magnitude of the reciprocal lattice vector | G z | as might be easily observed in experiment. The Weyl nodes have approximately the same energy below the Fermi level and are hence accessible by conventional ARPES. In addition, under external strain, the Weyl semimetal state is more robust than the sister compounds Td -WTe2 /MoTe2 . Our findings are important to explore Weyl fermion physics and useful for realizing possible applications of Weyl semimetal materials in future topological electronic devices.